Pengaruh Kepemimpinan Dan Lingkungan Kerja Terhadap Komitmen Organisasional Dan Kinerja Karyawan PT. Sumber Djantin Di Kalimantan Barat - Ahmad Shalahuddin (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2013)
Crumb Rubber has been one of mainstay industry in West Kalimantan since the wood processing industry declined in 2000 due to the reduced supply of raw materials. The importance of the rubber industry for the West Kalimantan Province development is shown by the large contribution of the rubber industry to the total value of exports of West Kalimantan. While every industry faces higher competition levels, so does industrial crumb rubber in West Kalimantan. The competition level faced not only at the regional level , but also at national and international levels . In order to improve the competitive advantages, a company engaged in the field of crumb rubber in West Kalimantan, in particular PT. Sumber Djantin, must conduct an evaluation or improvement in all areas to improve the performance of the company . One important element that should be improved is the performance of employees. Leadership and Work Environment is an important factor for improving the performance of employees. This study aims to examine and analyze the effect of Occupational and Environmental Leadership towards Organizational Commitment and Employee Performance PT. Sumber Djantin in West Kalimantan. Leadership and work environment are the exogenous variables in this study while organizational commitment as an intervening variable and employee performance as the endogenous variable. Sample of the study respondents totaled 150 production employees of PT. Sumber Djantin Kalbar. The analysis technique used in this study is variant-based Structural Equation Modeling ( SEM ), PLS, using SmartPLS software version 2.0 for windows . The results of study showed that leadership significantly influences organizational commitment, but does not significantly effect employee performance. Work environment significantly influences organizational commitment, but does not significantly effect on employee performance. Organizational commitment has a significant effect on employee performance.